Communities of knowledge and knowledge of communities: An appreciative inquiry into rural wellbeing - Kathleen May Kevany; Margaret MacMichael (Gateways, 2014)
This article offers a retrospective examination of the use of appreciative inquiry (AI) in a study on rural wellbeing. It provides a reflection on the rationale for choosing AI as a suitable methodology, critiques the application of AI in rural settings and considers its suitability for this inquiry into individual and community wellbeing. The article also considers the value of AI as a participatory research approach for community-university partnerships. A review of the literature on AI is distilled to examine the limitations as well as the utility of AI. Through an effective use of AI, communities of knowledge can be fostered and the knowledge of communities can be valued and harvested to enhance the wellbeing of rural communities.